SMEs ERP Readiness Success Factor Framework to Increase Implementation Successful Rate in Developing Countries – a Literature Review - Taufiq Maulana Firdaus; Haryasena Panduwiyasa; Widia Febriyani (International Journal of Innovation in Enterprise System, 2024)
ERP is a helpful tool for firms to conduct their daily operations because it can automate businessactivities. This tool has become more popular among SMEs because of the important benefits likereducing operational cost that can save time and money. However, due to its complex and technicaldifficulties to deploy, ERP systems might have unexpected implementation difficulties and result inmajor failure of ERP implementations. Therefore, the primary objective of this study is to develop acomplete framework designed to identify success and failure factors based on existing literatureresearch focusing on ERP implementations and its challenges faced by Small and Medium Enterprises(SMEs) in developing nations. This literature research explores the complexities of ERP deploymentby emphasizing critical failure factors (CFF) happened in developing countries as well as criticalsuccess factor (CSF) resulting in the alignment between each factor by using literature review methodfrom several publishers ranging from 2019-2024 from several publishers namely IEEE,ScienceDirect, Emerald Insights, SAGE, and Springer. With this sample size, new framework iscreated based on recent studies that aims to improve the implementation success rate in the context ofdeveloping countries by linking the relation from existing literature between critical success factorand critical failure factor and divide it into complexity and capacity dimension. To further help SMEsdifferentiate which dimension can reduce or increase the chance of successful rate of implementation,researchers create a modified TOPSIS matrix that can be used in SMEs ERP Readiness AssessmentMatrix.